A Study On The Causes Of Early Marriage In Patimuan Subdistrict, Cilacap Regency - Serli Dwi Putri; Sigid Sriwanto; Sutomo Sutomo (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study was aimed to determine the factors that cause early marriage in PatimuanSubdistrict, Cilacap Regency. This was a survey method with a population of 24 peoplewho underwent early marriage. The purposive sampling technique was conducted bytaking the female samples who underwent early marriage. An open questionnaire wasused as a data collection technique. Quantitative and qualitative methods were used in thedata analysis. The results showed that early marriage in Patimuan Subdistrict, CilacapRegency was caused by low economic capability, parental supervision, pre-maritalpregnancy, lack of education, religious teaching, customs, and promiscuity. The mostdominant factor causing the early marriage in Patimuan Subdistrict, Cilacap Regency wasparental supervision.